COMPARATIVE ANALYSIS OF AN ADMINISTRATIVE APPEAL IN CROATIAN, SLOVENIAN, AND EU LAW (EU and comparative law issues and challenges series (ECLIC), 2020)
In administrative matters, parties enforce their rights and legal interests against obligations before the administrative authority of first instance; furthermore, they can file an appeal to the second instance if they deem decisions as illegal or as an injustice done. Exhaustion of the appeal is in most legal systems as well as according to Croatian (2009) and Slovenian (1999) General Administrative Procedure Acts ((G)APA) as a procedural prerequisite to file further courts action, also in a situation of administrative silence with a negative act fiction. Besides said national GAPAs, the paper addresses draft EU Regulation (2016) as an EU APA too, in order to provide a comparative analysis of various acts. The right to good administration requires that administrative acts be taken by EU administration among others pursuant to timeliness and efficient legal protection. Based on normative national law analysis and case study focus of this paper is put on the administrative appeal, including through the lenses of an access to court. Paper provides an insight in Croatian, Slovenian, and EU APAs in prominent matter since it addresses constitutional and international principles of sound public governance. Authors establish that Croatian and Slovenian GAPAs provide an appropriate legal ground to achieve common European standards, yet they seem too detailed and fragmented in several dimensions; hence, EU APA can serve as a role model of their modernisation.